A professional's guide to data communication in a TCP/IP world - Carne, E. Bryan, 1928- (Artech House telecommunications library., 2004)
"This hands-on resource provides professionals with a comprehensive picture of the Internet protocol stack and the role of TCP/IP in data communication. It serves as a detailed guide to the protocols, networks, codes, signals, and equipment that make it possible to communicate using TCP/IP."--Jacket